Serum total adenosine deaminase activity in Nepalese patients with Rheumatoid Arthritis
Objective: Several studies indicate that serum adenosine deaminase (ADA) activity could be a potential marker for the diagnosis of patients with rheumatoid arthritis (RA). However, there has been no such study that could independently verify this finding in Nepali population. The present study therefore aims to measure the total ADA activity in the sera of Nepalese RA patients and verify its diagnostic potential. Materials and Methods: A total of 69 RA patients who visited Universal College of Medical Sciences Teaching Hospital (UCMSTH), Bhairahawa, Nepal for their medical treatment were enrolled for this study. An equal number of age and sex-matched healthy controls were also included in the study. Blood samples were collected from each study subjects and analyzed for serum total ADA, Creactive protein (CRP) and rheumatoid factor (RF). Results: Serum total ADA activity was found to be significantly (p<0.0001) higher (30.0